2012
DOI: 10.1002/jso.23201
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adequacy of lymph node yield in prophylactic unilateral central neck dissection for papillary thyroid carcinoma

Abstract: Length (or the longest measured dimension) of the fresh CLN specimen was the only factor assuring LNY ≥ 6. Surgical complications and short-term outcomes appeared similar between LNY <6 or ≥ 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Thyroid cancer staging systems also indicate age as a prognostic factor [40]. A number of studies showed that PTC patients older than 45 years have poor prognosis [2,4,6,9,11,12]. However, several studies also indicated worse prognosis and the presenece of lymph node and distant metastasis in younger PTC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid cancer staging systems also indicate age as a prognostic factor [40]. A number of studies showed that PTC patients older than 45 years have poor prognosis [2,4,6,9,11,12]. However, several studies also indicated worse prognosis and the presenece of lymph node and distant metastasis in younger PTC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of thyroid cancer is papillary thyroid cancer (PTC), representing 85% of all thyroid cancer cases [1]. According to the data from "Cancer Facts and Figures, 2016" , thyroid cancer was diagnosed in over 64,000 individuals in 2016 in the U.S.A, and the incidence rate increased approximately 5% in the last 10 years [2,3]. Although PTC is a slowly growing tumor and has an excellent prognosis, with expected 5-year survival greater than 98%, histological subtypes of PTC such as columnar cell variant (CCV), tall cell variant (TCV), and diffuse sclerosing variant (DSV) have a relatively worse prognosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was interesting to note the incidence of central LNM varied widely from 23.5% to 82.4% between studies. Perhaps, this was also a reflection of the quality of preoperative USG assessment and might also have been a result of differences in the extent of the pCND and quality of the histological examination between studies (5,30,31). Also similar to previous meta-analyses,(9-11) we found the temporary hypocalcemia to be significantly higher in group A than B (26.0% vs. 10.8%, respectively; OR=2.56;95%CI=2.04 -3.21).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of metastatic DTC in adults identified a mean (SD) lymph node yield of 41.0 (12.1) (range 27–66) 17 . Adequate unilateral lymph node yield from the central neck has been defined as six or more 18 . Results suggest that children and adults have a similar number of lymph nodes, that a similar number of lymph nodes can be resected during neck dissection, and that results from the present study are likely based on an adequate sample of nodal tissue.…”
Section: Discussionmentioning
confidence: 99%